Analisis Deskriptif Perbandingan Rasio Likuiditas Bank Syariah Sebelum Dan Di Masa Pandemi Covid-19 - Andika Sepriyadi; Dela Safitri; Rotipa Aulia; Rizky Hariyadi; Miti Yarmunida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study is to compare the liquidity ratios of Islamic banks before and during the covid-19 pandemic. This study uses qualitative research methods and the data source used is secondary data taken from the financial statements of Islamic banks which are the object of research. The results showed that there were Islamic banks that experienced an increase and decrease in FDR from the previous year, Islamic banks that experienced an increase were Bank Bukopin Syariah and BTPN Syariah, while those that experienced a decrease in FDR were Bank Mega Syariah, BCA Syariah and Bank Muamalat. On CR Bank Mega Syariah, BCA Syariah and Bank Muamalat increased , the component R asio remain in a healthy state as the previous year . S hile Bank Syariah Bukopin and Bank Syariah Bank experienced a significant decline seen from its declining ratio. QR BCA Syariah, Bank Bukopin Syariah and BTPN Syariah experienced an increase during the pandemic compared to the previous year as indicated by their ratios that were in a healthy condition, while Bank Mega Syariah and Bank Muamalat did not experience an increase in their ratios as indicated by ratios that were in an unhealthy condition. Keywords: FDR, CR, QR, Covid-19, Liquidity